Endoscopic excision of a tympanic paraganglioma: Training the next generation of ear surgeons - Natasha Pollak (KeAi Communications Co., Ltd., 2017)
Tympanic paragangliomas are uncommon vascular tumors of neural crest origin. Classically these lesions have been surgically managed via a transcanal or transmastoid approach using binocular microscopy. We describe a case in which a tympanic paraganglioma was removed via a transcanal approach, using the endoscope exclusively. Endoscopic ear surgery enhances visualization, helping to ensure complete tumor removal, while reducing unnecessary dissection and its associated morbidity. For small middle ear neoplasms, a purely endoscopic approach is feasible, with excellent results. Resident education in ear surgery has also been enhanced by the use of endoscopes. The wide field of view provided by the endoscope helps trainees understand the intricate three-dimensional anatomy of the middle ear cleft.